2021
DOI: 10.1016/j.surg.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous iron supplementation after liver surgery: Impact on anemia, iron, and hepcidin levels—a randomized controlled trial

Abstract: Background: Anemia is a recognized risk factor for perioperative related morbidity and mortality and is frequently reported in liver surgeries with an estimated incidence of 32%. We aim to assess the impact of intravenous iron administration in the immediate postoperative period on anemia and iron status as well as to determine the kinetics of hepcidin after liver surgery. Methods: The HepciFer trial, a randomized controlled trial, included 50 patients undergoing liver surgery. In accordance with the randomiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Moreover, the delta change of the iron metabolism variables between the iron-treated and the placebo groups of patients also significantly improved in the former patients compared to the latter. These findings are consistent with previous investigations conducted in patients with liver surgery and anemic diseases [28,[51][52][53]. Collectively, these results suggest that iron replacement favored the optimization of iron metabolism even in non-anemic patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the delta change of the iron metabolism variables between the iron-treated and the placebo groups of patients also significantly improved in the former patients compared to the latter. These findings are consistent with previous investigations conducted in patients with liver surgery and anemic diseases [28,[51][52][53]. Collectively, these results suggest that iron replacement favored the optimization of iron metabolism even in non-anemic patients.…”
Section: Discussionsupporting
confidence: 92%
“…Collectively, these results suggest that iron replacement favored the optimization of iron metabolism even in non-anemic patients. Interestingly, no significant differences were seen in IL-6 levels after treatment with iron, findings that had also been previously reported [51].…”
Section: Discussionsupporting
confidence: 87%
“…19 The HepciFer trial, a randomized controlled trial, which included 50 patients undergoing liver surgery concluded that intravenous ferric carboxymaltose administration did not result in a significant increase of hemoglobin levels 7 days after surgery. 34 This study had additional limitations that should be considered when interpreting the results. The limited number of patients with severe anemia restricted evaluation of the risk of severe complications Fifteen risk adjustment factors (described in Section 2) were used to calculate riskadjusted odds ratios based upon anemia severity.…”
Section: Discussionmentioning
confidence: 94%
“…However, inflammatory status can inhibit erythropoiesis directly and indirectly, reducing sTfR levels, being less reliable with higher degrees or inflammation 19 . Besides, although some studies showed changes in sTfR after IV iron treatment, 28 sTfR is not widely used due to lack of standardization and variations in assay types.…”
Section: Discussionmentioning
confidence: 99%